A Comparative Study of the Rulings about Animal Organs in Judaism, Christianity and Islam - Irfan Ullah; Uzma Siddiq (Journal of Islamic and Religious Studies, 2016)
Almighty Allah bestowed honors and respect to mankind. Keeping in view the honor of mankind, Allah SWT blessed them also a purified, cleanse and Halal [permissible & Lawful] food. Moreover, the religious teachings are very clear and transparent in this regard to highlight the difference between what is beneficial and useful for them and what is harmful and injurious. Almighty Allah is very kind and compassionate to his servants and described definite commands and orders about such Animals which are adequate and effective to mankind and counts them in Halal category and otherwise are considered Restricted and Haram [impressible & unlawful]. So all kinds of animals which are harmful are prohibited with exception of their some body organs and which are useful are described with their all qualities are halal in mentioned divine religions i.e. Judaism, Christianity and Islam coupled with little changes in rulings about the use of body organs of impermissible animals like use of bones or skin etc. The paper emphasis on describing the disparities of three divine religions regarding the use of organs, skin of animals, bones and highlight their procedures of making them safe and useable for mankind. This study will lead us to know that which divine religion is more applicable and provides cleanse food to their followers along with having the status of eternity strength among three.